Performans Produksi Telur Dan Pendapatan Usaha Itik Alabio Petelur Dalam Pemanfaatan Bekicot Pohon Fermentasi (Achatina Sp.) - Danang Biyatmoko (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2014)
The goal of this research is to analyze the effect of tree snail fermentation performance to production and profits of Alabio ducks. This research consist of two steps, step I want to know to make TBF of achatina by fermentation process and nutrition analyze TBF product fermentation of achatina, and step II using feeding trial TBF in Alabio duck rations using completely randomized design (RAL) 4 treatments and 4 replicateds, followed by DMRT test. The treatment step II consist of : R0 = control (without TBF in rations); R1 = level 7.5% TBF in rations; R2 = 15 % TBF in rations dan R3 = 22.5% TBF in rations. Result of this research showed in Step I TBT product fermentation of achatina was safe and can increased can increasing quality of nutrition, mainly protein until 38.0 % from 30.56 % before fermentation nutrition. Result in Step II showed the treatment no significant increase egg production but an increase in levels of up to 22.5% TBF TBF (R3) tends to increase egg production, while the eggmass also showed no significant effect , but treatments were using TBF over 7.5% in ration that was R3 (15%) and R4 (22.5%) can increasing eggmass bigger than control. The treatment showed that level of 22.5 % TBF in rations was the biggest increasing IOFC (Income over feed cost) about Rp. 7.316,-/kg from selling of egg Alabio duck layer. This research was recomendate that the treatment R3 with 22.5% TBF in ration was the best treatment to increased all the parameter and the price of formulated ration was the lowest about Rp. 3234,-/kg.